Iridicycle-Catalysed Imine Reduction: An Experimental and Computational Study of the Mechanism - Chen, Hsin-Yi Tiffany; Wang, Chao; Wu, Xiaofeng; Jiang, Xue; Catlow, C. Richard A.; Xiao, Jianliang (Chemistry : a European journal, 2015)
The mechanism of imine reduction by formic acid with a single‐site iridicycle catalyst has been investigated by density functional theory (DFT), NMR spectroscopy, and kinetic measurements. The NMR and kinetic studies suggest that the transfer hydrogenation is turnover‐limited by the hydride formation step. The calculations reveal that, amongst a number of possibilities, hydride formation from the iridicycle and formate probably proceeds by an ion‐pair mechanism, whereas the hydride transfer to the imino bond occurs in an outer‐sphere manner. In the gas phase, in the most favourable pathway, the activation energies in the hydride formation and transfer steps are 26–28 and 7–8 kcal mol−1, respectively. Introducing one explicit methanol molecule into the modelling alters the energy barrier significantly, reducing the energies to around 18 and 2 kcal mol−1 for the two steps, respectively. The DFT investigation further shows that methanol participates in the transition state of the turnover‐limiting hydride formation step by hydrogen‐bonding to the formate anion and thereby stabilising the ion pair. Workin’ on an imine: Transfer hydrogenation of imines by formic acid with a single‐site iridicycle catalyst has been investigated by density functional theory (DFT), NMR spectroscopy and kinetic measurements. The mechanism is shown to be turnover‐limited by the hydride formation step, the barrier of which is significantly lowered by a protic solvent (see scheme; RDS=rate‐determining step).